Penerapan Google Classroom Application untuk Meningkatkan Hasil Belajar Ekonomi - Yosi Shandra (Ikhtisar: Jurnal Pengetahuan Islam, 2022)
The main problem in this study is how to increase the use of the Google Classroom application to improve student economic learning outcomes. This study aims to determine the improvement of economic learning outcomes for class X students by using the Google Classroom application at SMAN 10 Padang. The research method is Classroom Action Research (CAR). The research procedure includes four stages, namely planning, implementation, observation, and reflection. The research subjects were 36 students of class X SMAN 10 Padang in the academic year 2020/2021 in odd semesters. The research instrument used was a multiple choice test and a questionnaire on the use of the Google Classroom application. The research data shows that the average score of economic learning outcomes on cooperative material for class X SMAN 10 Padang using the Google Classroom application is 86,10 and is in the very good category.